2016
DOI: 10.1002/cncr.30519
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of multidomain decline in health‐related quality of life after stereotactic body radiation therapy (SBRT) for prostate cancer

Abstract: Prostate SBRT has minimal long-term impact on multidomain decline, and the majority of more significant multidomain declines appear to be unrelated to treatment. This emphasizes the importance of focusing not only on the side effects of prostate cancer treatment but also on other comorbid illnesses that contribute to overall HRQOL. Cancer 2017;123:1635-1642. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It is generally recognized that when assessing PROs, a change in these functions exceeding half of a standard deviation is a minimal important difference (29). Other investigators have suggested using other measures, such as 2 times the minimal important difference (33, 34). In this study, as per the National Cancer Institute (NCI)-approved protocol, we have reported on the results based on a change in PROs of greater than half of a standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recognized that when assessing PROs, a change in these functions exceeding half of a standard deviation is a minimal important difference (29). Other investigators have suggested using other measures, such as 2 times the minimal important difference (33, 34). In this study, as per the National Cancer Institute (NCI)-approved protocol, we have reported on the results based on a change in PROs of greater than half of a standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported predictors of HRQOL years after radiation therapy for nonmetastatic prostate cancer. One of those studies revealed that baseline bowel issues and a depression diagnosis were independent predictors of HRQOL decline following stereotactic body radiation therapy (commonly known as CyberKnife) in prostate cancer men [ 16 ]. One study clearly described the trajectories of common symptoms reported by patients before, during, and after radiation therapy for prostate cancer [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms persist for 12–24 months following EBRT completion [ 12 , 13 ]. However, the reported short-term and long-term effects of these symptoms on HRQOL for this clinical population are inconsistent [ 3 , 11 , 13 16 ], most likely related to differences in the instruments and approaches used to measure HRQOL.…”
Section: Introductionmentioning
confidence: 99%
“…This article is protected by copyright. All rights reserved SBRT is convenient and cost-effective relative to conventional EBRT courses of 8-9 weeks (7,8), with a promising overall toxicity profile (9)(10)(11), that currently is being investigated in numerous randomized trials that have either already reported early results or finished accrual (12, 13).…”
Section: Author Manuscriptmentioning
confidence: 99%